Coenzyme Q10 and its effects in the treatment of neurodegenerative diseases - Santos, Graciela Cristina dos (2009)
According to clinical and pre-clinical studies, oxidative stress and its consequences may be the cause or, at least, a contributing factor, to a large number of neurodegenerative diseases. These diseases include common and debilitating disorders, characterized by progressive and irreversible loss of neurons in specific regions of the brain. The most common neurodegenerative diseases are Parkinson's disease, Huntington's disease, Alzheimer's disease and amyotrophic lateral sclerosis. Coenzyme Q10 (CoQ10) has been extensively studied since its discovery in 1957. It is a component of the electron transportation chain and participates in aerobic cellular respiration, generating energy in the form of adenosine triphosphate (ATP). The property of CoQ10 to act as an antioxidant or a pro-oxidant, suggests that it also plays an important role in the modulation of redox cellular status under physiological and pathological conditions, also performing a role in the ageing process. In several animal models of neurodegenerative diseases, CoQ10 has shown beneficial effects in reducing disease progression. However, further studies are needed to assess the outcome and effectiveness of CoQ10 before exposing patients to unnecessary health risks at significant costs.